Role of ascorbic acid infusion in critically ill patients with transfusion‐related acute lung injury. Issue 5 (7th January 2022) - Kassem, Amira B.; Ahmed, Islam; Omran, Gamal; Megahed, Mohamed; Habib, Tamer
Abstract : Introduction: In critically ill patients, transfusion‐related acute lung injury (TRALI) remains the leading cause of transfusion‐related fatalities in critical care settings and is associated with inflammation and oxidative stress state. Recent research raised the potential efficacy of high‐dose intravenous ascorbic acid (VC) in critically ill patients. Objective: The aim of this trial was to investigate the effect of high‐dose intravenous VC as a targeted therapy for TRALI in terms of serum proinflammatory (interleukin [IL]‐8, IL‐1β, C‐reactive protein), anti‐inflammatory (IL‐10), oxidative stress (superoxide dismutase, malondialdehyde) markers, and plasma VC levels. Secondary outcomes were oxygenation (PaO2 /FiO2 ratio), vasopressor use, duration of mechanical ventilation, ICU length of stay, 7‐day mortality and 28‐day mortality. Methods: Eighty critically ill patients with TRALI (n = 80) were randomized to receive 2.5 g/6 h intravenous vitamin C for 96 hours (ASTRALI group) or placebo. Patients were followed up to measure the outcomes initially (T0) and at the end of treatment (T96). Results: When compared to the control group, the ASTRALI group at T96 showed significantly higher median of IL‐10 (31.6 ± 25.8 vs 17.7 ± 12.0 pg/mL, P <  .0001) levels and superoxide dismutase (12 876 ± 4627 U/L vs 5895 ± 6632 U/L, P <  .0001) activities, and lower median C‐reactive protein (76 ± 50 vs 89 ± 56 mg/L, P =  .033), IL‐8 (11.8 ± 7.3 vs 35.5 ± 19.8 pg/mL, P <  .0001) and malondialdehyde (0.197 ± 0.034 vs 0.234 ± 0.074 μM/L, P =  .002) levels. Conclusion: High‐dose ascorbic acid was associated with significantly reduced oxidative stress, reduced pro‐inflammatory markers except IL‐1β, elevated anti‐inflammatory marker and elevated plasma VC levels.